INDONESIA’S ECONOMY DIPLOMACY: STRATEGIC OPPORTUNITY IN PPE PRODUCTION IN PANDEMIC ERA - Fadhilah Permata Nira; Fahrizal Lazuardi; Ferdian Ahya Al Putra; Zia’ulhaq As Shidqi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The COVID-19 pandemic has had a major impact on the world order, especially on the health and economic sectors. The World Health Organization (WHO) noted that as of 4th December 2020, positive cases of COVID-19 in the world reached more than 64 million confirmed cases, and 1.5 million death cases. Responding to this condition, the world's attention has turned to efforts to produce vaccines. However, apart from vaccines, the world demand for Personal Protective Equipment (PPE) has also continued to increase, and even, the world experienced a shortage of PPE. In this case, Indonesia as a producer of PPE can take advantage of this momentum to earn economic benefits in the midst of this pandemic. PPE made in Indonesia produced by PT Sri Rejeki Isman Tbk has obtained ISO 16604 Class 3 certification at Intertek HQ, Cortland, New York. PPE is a nubic garment or CBRN (Chemical Biological Radiation) that can be used for both pandemic and non-pandemic needs. This research will discuss Indonesia's PPE diplomacy in the pandemic era. This study uses economy diplomacy theory and qualitative methods to analyze Indonesia's opportunities through PPE diplomacy. The results showed that the contribution of PPE and mask exports reached US$ 4.56 billion. Therefore, this paper assesses that PPE is economically more strategic than vaccines. Indonesia has a great opportunity to generate concrete benefits from economy diplomacy through the production of domestic PPE or what can be called PPE diplomacy. Key words: COVID-19, economy diplomacy, PPE